Acceptance Of Sergeant-Level Principals In Elementary Schools Acceptance Level, Strategies And Challenges - Yani, Dwi; Hadi, Syamsul; Pristiani, Riska (UNIVERSITAS PAKUAN, 2024)
This study aims to describe the acceptance of sergeant-level principals (serious but relaxed), the strategies used to obtain acceptance, and the challenges faced. This research approach uses the Grounded Theory Strauss Corbin method with an analysis of the internal views of school residents and the external views of the school environment. Data were collected through in-depth interviews and participatory observation in three elementary schools in Mojokerto Regency. The results showed variations in the acceptance rate of sergeant levels, effective strategies used by school principals, and significant challenges faced in the admissions process. These findings provide important insights to improve the effectiveness of new school leadership